Audio Visual Based Scenario of Kondobuleng Performances as A Learning Formula for Actors and Potential of Performing Art Tourism - Muhajir; Ferawaty Syam; Muh. Fadhly Kurniawan (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2023)
This research is a form ofstrategy to preserve Kondobulengtheater through the process of transforming print-based scenarios into audio-visual-based digital scenario. The urgency of this research is due to the lack of regeneration of actors in the Kondobuleng theater which has become oneof the causes of the dimness of the Kondobuleng theater group which then has an impact on the Nusantara art tourism sector. In addition, the actors are known to be in a phase that is quite difficult to transfer knowledge of Kondobuleng performances, especially on scenario. Therefore, this research provides a solution by creating a supporting media to facilitate the process of transmitting knowledge related to Kondobuleng theater performances. The method used is the documentation through cinematography technique. These efforts produce new media so as to produce academic novelty in the form of product in the form of audio-visual-based digital scenariosin Kondobuleng theater, especially in the world ofperforming arts. This new media can be used as a medium for learning and actor training in understanding plot, dialog, texture, mimicry, and artistic sets in a performance. To measure the effectiveness of the output product, a survey was conducted from the product trial using the action research (AR) method and structured interviews to several theater actors to avoid subjectivity in the assessment of theproduct findings. On the other hand, this research is usefulas a solution to the threat of regeneration crisis in the Kondobuleng theatre as well as creating artistic spaces thathave the potential to impact on the tourism industry sector of the performing arts world.